Pathogenesis of Cluster Headache: From Episodic to Chronic Form, the Role of Neurotransmitters and Neuromodulators. Issue 9 (11th October 2019) - D'Andrea, Giovanni; Gucciardi, Antonina; Perini, Francesco; Leon, Alberta
Abstract : Objective: To describe the role of biochemical anomalies of tyrosine (TYR), tryptophan (TRP), and arginine (ARG) metabolism in patients suffering from episodic and chronic cluster headache (CCH). Background: The pathogenesis of cluster headache (CH) and the process that transforms the episodic into the chronic form are unknown. However, the accompanying symptoms suggest a dysfunction of the sympathetic system and hypothalamus along with anomalies of metabolism of catecholamines, elusive amines, and nitric oxide (NO) metabolism. Methods: We describe the results obtained from the last papers published on this issue. The level of metabolites were analyzed by different high‐performance liquid chromatography methods. Results: In both episodic and CH patients, the levels of dopamine and elusive amines are very elevated. The only biochemical difference found in studies between episodic and chronic cluster was that norepinephrine levels were significantly lower in episodic cluster in comparison to control and chronic subjects. In addition, the levels of ARG, homoarginine, and citrulline, precursors of synthesis of NO, were significantly lower in chronic cluster. Conclusions: All these results suggest that TYR, TRP, and ARG metabolism is abnormal and may constitute a biochemical fingerprint of CH patients. The increased levels of norepinephrine in chronic cluster constitute a possible cause of chronicity of this primary headache. The high levels of tryptamine and its activity on the central serotoninergic system may explain why the length of CH is brief in comparison to migraine and tension‐type headache. The low levels of ARG, homoarginine, and citrulline may be the consequence of high circulating levels of α1 ‐agonists, such as epinephrine and norepinephrine, and their biochemical interaction with endothelial trace amine‐associated receptor 1 that induces activation of NO synthase, resulting in NO synthesis in the circulation, NO release, intense vasodilation, and as a result, the cluster attack.